Effects of alloying elements on the electrochemical behaviors of Al-Mg-Ga-In based anode alloys. (3rd May 2019) - Li, Li; Liu, Hui; Yan, Yang; Zhu, Hualong; Fang, Hongjie; Luo, Xier; Dai, Yilong; Yu, Kun
Abstract: In this study, in order to investigate the effects of alloying elements on the electrochemical behaviors of Al-based anodes, pure Al and Al-Mg-Ga-In alloys with different compositions (Al-0.25Mg-0.3Ga-0.3In, Al-1Mg-0.05Ga-0.15In and Al-2Mg-0.15Ga-0.05In (wt%)) were fabricated. The microstructure, corrosion behavior, electrochemical property, discharge performance and corroded morphology of the four experimental anodes were studied. Al-Mg-In-rich intermetallic compounds were observed in Al-Mg-Ga-In alloys. The results of the polarization curve and electrochemical impedance spectroscopy indicate that the addition of Mg acts as a critical component in improving the discharge activity of Al-based anode and contributes to a more negative electrode potential. According to the corrosion morphologies after discharge, it can be concluded that the addition of In element plays an essential part in forming corrosion pits on the surface of the anode while the addition of Ga element plays a vital role in destroying the surface passive layer to prevent passivation once corrosion starts. Highlights: Increasing Mg amount does activate Al-based anodes significantly. Ga has a major contribution in activating anode than In. In plays an essential part in forming corrosion pits. Ga activates the surface of anodes and affects the morphology of corrosion products. Al-2Mg-0.15Ga-0.05In alloy shows the best electrochemical performance as Al-based anode.